Pengukuran Kecepatan Aliran Bermuatan Sedimen di Saluran Irigasi - Saiful Rochdyanto (agriTECH, 1994)
Study on the measurement of flow velocity in sediment-laden flow was carried out in Van Der Wig* irrigation Canal, Yogyakarta. Study was conducted in various of canal conditions and various of sediment concentration. Flow velocity was measured by using current meter and water sample was collected by using suspended sampler. Result of study shows that velocity distribution data can be suited by the power-law, although it does not seem to fit with equation that presented by Munson which is suitable with non-sediment laden flow in open channels. Due to the deviation on power-law graph, in order to find the average-measured-velocity which is match with the actual-velocity, the point of measurement should be 0,71 D (from the free water surface). The point of measurement at 0,6 J) such as already established by regulation will give an error about 14,35%.